Persepsi Mahasiswa Tentang Pelaksanaan Mata Kuliah Restoran dan Catering di Prodi Pendidikan Kesejahteraan Keluarga Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang - Vanesha Padlin; Elida Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
This study aims to describe: 1) Students perceptions about the implementation of Restaurant and Catering courses as a whole, and 2) Students perceptions about Restaurants and Catering courses based on research indicators. This type of research is a quantitative descriptive study. The study population consisted of 48 students from the Family Welfare Study Program at the State University of Padang with a total sample of 48 people taken based on total sampling technique. Data sources are students who have taken Restaurants and Catering courses. The technique of collecting research data is done by using a questionnaire that is designed based on a Likert scale and has been tested for validity and reliability. Data analysis technique is done by determining the frequency distribution of data and data classification techniques based on the calculation of scores using the ideal average research formula (Mi) and standard deviation (Sdi). The results of this study illustrate: 1) Student perceptions about the implementation of Restaurants and Catering courses as a whole are in the very low category, and 2) Student perceptions about the implementation of Restaurants and Catering courses based on three research indicators are in the medium category. Based on the results of the study it can be concluded that the family welfare education student at Padang State University has a very low perception of the subject.